Preparation of Land Use Zoning Maps of Chaumala VDC, Kailali - Chalise, Devraj; Joshi, Abhasha; Twanabasu, Bikesh; Rawal, Nabin; Amgai, Saroj (International Journal of Applied Sciences and Biotechnology, 2017)
To characterize soils of different land uses and to prepare land use zoning maps, a field survey was conducted in August, 2014 in Chaumala VDC, Kailali. Main objective was to prepare scientific land resource inventory at VDC level to delineate land use based on land types, associated soils and land capability classes to formulate sustainable land use planning. The maximum area is allocated in forest zone (66.62%) followed by agriculture zone (20.83%). Area allocated as public use is 9.48%, for residential is 2.91%, and for commercial is 0.15% whereas industrial area covers the minimum (0.01%). Detailed land resource inventory is utmost for better land use planning and formulating best land use policies. Int J Appl Sci Biotechnol, Vol 4(4): 458-463